Ocena ustreznosti normativnih podatkov za test škatle in kock za vzorec otrok v Sloveniji - Zernec, Sara (Rehabilitacija (Ljubljana), 2021)
Introduction: The Box and Block Test is a validated instrument for evaluation of gross manual dexterity and coordination. The test material consists of a wooden box with 150 wooden cubes of different colors. The goal of the test for a participant is to transfer as many cubes as possible, one at a time, from one compartment to the other, in the time one minute. The purpose of the study was to evaluate if the normative scores of the Box and block test from the Netherlands could be used also for children in Slovenia. Methods: The study included 30 healthy children (15 girls and 15 boys), from six to seven years of age. All of the participants were right-handed. Their scores on the Box and Block Test were compared to normative scores from the Netherlands. Results: On average, girls transferred 38.9 cubes with their right hand and 37.6 cubes with their left hand. Boys transferred 43 cubes with their right hand and 42.4 cubes with their left hand. On average, the children in the pooled sample transferred 40.9 cubes with their right hand and 40 cubes with their left hand, which is statistically significantly fewer than in the comparable group of children from the Netherlands, even after correcting the scores for dominant hand. Conclusion: These results bring us to the conclusion that we need to repeat the evaluation with the Box and Block Test in a larger group of children, within all age groups and perhaps develop our own norms for the test.
Keywords: assessment; Box and Blocks test; Child; hand; ocenjevanje; otrok; roka; Test škatle in kock; Upper Extremity